Pemanfaatan Lentera Nagari sebagai Taman Baca Bagi Anak di Tapan Pesisir Selatan - Putri, Regina Ferani; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThis paper discusses about the Utilization of a Lentera Nagari As a reading room For Children In Tapan South Pesisir. This study aims to; (1) Describe the profile of the Lentera Nagari in Tapan South Pesisir; (2) Describe the constraints and efforts made party Lentera Nagari in the utilization of the Park Read for the child; (3) Describe the impact faced by the Lentera Nagari in the utilization of a reading garden Â for children in Tapan district of South Pesisir.Â The method used is descriptive method. Data were collected through observation and direct interviews with the officers of the Lentera Nagari in Tapan South pesisir.Keyword: Â Reading Garden, child